2021
DOI: 10.3233/idt-200013
|View full text |Cite
|
Sign up to set email alerts
|

A TOPSIS-ELM framework for stock index price movement prediction

Abstract: In recent years Extreme Learning Machine (ELM) has gained the interest of various researchers due to its superior generalization and approximation capability. The network architecture and type of activation functions are the two important factors that influence the performance of an ELM. Hence in this study, a Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) oriented multi-criteria decision making (MCDM) framework is suggested for analyzing various ELM models developed with distinct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A systematic survey on recent trends in stock market prediction by Jiang ( 2021 ) revealed that researchers have used various classification as well as regression metrics to evaluate the performance of stock market prediction models. As suggested by (Kou et al 2012 ; Samal and Dash 2021a ), if the performance of a model is evaluated over multiple criteria, a robust performance evaluation system can be generated. To empirically authenticate their proposal, the authors (Kou et al 2012 ) evaluated the performance of 11 different classification schemes over 10 performance evaluation criteria using MCDM techniques such as TOPSIS, ELECTRE, grey relational analysis, VIKOR, PROMETHEE.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic survey on recent trends in stock market prediction by Jiang ( 2021 ) revealed that researchers have used various classification as well as regression metrics to evaluate the performance of stock market prediction models. As suggested by (Kou et al 2012 ; Samal and Dash 2021a ), if the performance of a model is evaluated over multiple criteria, a robust performance evaluation system can be generated. To empirically authenticate their proposal, the authors (Kou et al 2012 ) evaluated the performance of 11 different classification schemes over 10 performance evaluation criteria using MCDM techniques such as TOPSIS, ELECTRE, grey relational analysis, VIKOR, PROMETHEE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The weights of individual base classifiers were assigned based on their respective TOPSIS ranking. More recently in Samal and Dash ( 2021a ), 15 different activation function-based ELM frameworks have been evaluated based on 16 criteria for the prediction of stock index price movements. It is reported that MCDM-based evaluation of classifiers can provide a more robust and reliable outcome.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations